Consumers’ purchase propensity for pasta tracked with blockchain technology and labelled with sustainable credence attributes - Petrontino, Alessandro; Frem, Michel; Fucilli, Vincenzo; Tria, Emanuela; Campobasso, Adele Annarita; Bozzo, Francesco (Frontiers in Sustainable Food Systems, 2024)
Pasta is a key product in Italy's agri-food industry, consumed due to its ease of preparation, nutritional richness, and cultural importance. Evolving consumer awareness has prompted adaptations in the pasta market, to address concerns about social, environmental, quality, and food safety issues. This study examines Italian consumers' willingness to pay (WTP) for pasta in local markets, analysing their behaviours and preferences. For this purpose, we used a discrete choice experiment (DCE) technique combined with a latent variable model. We also collected 397 valid online questionnaires. The results reveal an interest utility among all respondents to pay a price premium of €1.16, €0.82, €0.62, €0.41, and €0.36 for 500 g of pasta, for the use of blockchain/QR code (BC) technology on the label, providing data on credence attributes such as safety, environmental and social sustainability as well as business innovative practices, respectively. As such, this research has private and public implications. On one hand, this research may bridge the scarcity in studies regarding consumer preferences and WTP for BC in the pasta value chain, preventing agricultural frauds, ensuring the sustainability and quality of agrifood products like pasta, and protecting and educating consumers through clear and transparent information. On the other hand, this research may incentivise pasta businesses to meet social and environmental consumers' demands while simultaneously enhancing their financial performance.